Copper Triflate: An Efficient Catalyst for Direct Conversion of Secondary Alcohols into Azides - Khedar, Poonam; Pericherla, Kasiviswanadharaju; Kumar, Anil (Synlett, 2014)
A simple, practical, and efficient strategy has been demonstrated for the direct synthesis of organic azides from alcohols using azidotrimethylsilane (TMSN3) as azide source in the presence of copper(II) triflate [Cu(OTf)2]. A variety of alcohols was converted into the corresponding azides in good to excellent yields. The formation of an intermediate carbocation was confirmed by the synthesis of bis(diphenylmethyl) ether.
Keywords: azides; azidotrimethylsilane; copper triflate; Lewis acid